ANALISIS STRATEGI PEMASARAN TERHADAP PENJUALAN PRODUK UMKM KULINER STUDI KASUS PADA “FIOR FIORE PATISSERIE” BANDAR LAMPUNG - Daud, Syahril; Yanra, Tania Permata; Shabrina, Dea Nurullyah; Naufal, Ahmad Ghani (LP2M Universitas Bina Bangsa, 2025)
The culinary industry significantly contributes to Indonesia's economy. In facing intense competition, MSMEs, including Fior Fiore Patisserie, require effective marketing strategies to maintain and enhance their competitiveness. This study aims to analyze the application of the marketing mix strategy (product, price, place, promotion) at Fior Fiore Patisserie and identify the factors influencing its success. A qualitative research method was employed, utilizing data collection techniques such as direct observation of the business location and interviews with the business owner. The findings reveal that Fior Fiore's marketing strategies include strategic location selection, the use of high-quality ingredients, product innovation that aligns with trends, and leveraging social media to reach a broader market. These strategies successfully built brand image, attracted customers, and increased sales. However, the study also identified challenges such as limited performance evaluation, potential conflicts among team members, and restricted market segmentation due to premium-priced products made with high-quality ingredients. To address these challenges, recommendations include optimizing performance management, diversifying product offerings, implementing flexible pricing strategies, expanding online sales channels, and developing customer loyalty programs. These findings are expected to serve as a guide for other MSMEs in developing competitive marketing strategies in the culinary industry.